2020
DOI: 10.1016/j.hrthm.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of the PR interval with increasing heart rate in patients with COVID-19

Abstract: BACKGROUND Myriad manifestations of cardiovascular involvement have been described in patients with coronavirus disease 2019 (COVID-19), but there have been no reports of COVID-19 affecting the cardiac conduction system. The PR interval on the electrocardiogram (ECG) normally shortens with increasing heart rate (HR). The case of a patient with COVID-19 manifesting Mobitz type 1 atrioventricular (AV) block that normalized as the patient's condition improved prompted us to investigate PR interval behavior in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 23 publications
2
33
1
Order By: Relevance
“…Pavri et al have recently shown around 50% of adult patients with COVID-19 had an abnormal PR:HR slope, which correlated with the worst clinical outcomes. 17 This finding occurred in 25% of our cohort, however, our data showed no correlation with either ICU admission or inotropic support.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Pavri et al have recently shown around 50% of adult patients with COVID-19 had an abnormal PR:HR slope, which correlated with the worst clinical outcomes. 17 This finding occurred in 25% of our cohort, however, our data showed no correlation with either ICU admission or inotropic support.…”
Section: Discussioncontrasting
confidence: 57%
“… 16 In patients with a ≥5 bpm difference in heart rate in ≥2 ECGs, a positive slope, with paradoxical lengthening of PR interval at increasing heart rates, was defined as abnormal PR:HR slope. 17 QRS prolongation is the QRS duration over 98th percentile for age and sex. 16 Prolonged corrected QT interval is the QTc over 98th percentile for age and sex.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac involvement has been reported with varying incidence as one of the manifestations that confer a worse prognosis [2]. It has been reported that there was a correlation between paradoxical prolongation or lack of shortening of the PR interval with increasing heart rate and higher mortality and intubation rate in COVID-19 patients, suggesting a worse prognosis when conduction abnormalities are present [3]. Cardiac arrhythmias have been reported in association with cardiac injury [2,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Another study analyzing the ECGs of 75 COVID-19 patients showed that abnormal PR interval behavior (paradoxical prolongation or lack of shortening) with increasing heart rate was associated with increased risk of death (29.7% vs 7.9%, p =0.019) and need for endotracheal intubation (43.2% vs. 21.1%, p =0.05) compared to patients with PR interval shortening [20] .…”
Section: Bradycardia/conduction Disturbancesmentioning
confidence: 99%